Tailoring the near-field guiding properties of magnetic metamaterials with two resonant elements per unit cell - Sydoruk, O; Radkovskaya, A; Zhuromskyy, O; Shamonina, E; Shamonin, M; Stevens, C; Faulkner, G; Edwards, D; Solymar, L (2006)
A theoretical and experimental study of magnetic metamaterials with unit cells containing two resonant elements is presented. The properties of these structures, consisting of split rings, are governed by strongly anisotropic magnetic coupling between individual elements. This coupling leads to propagation of slow magnetoinductive waves in the vicinity of the resonant frequency. The wavelength of magnetoinductive waves is much smaller than the free-space wavelength of the electromagnetic radiation. This opens up the possibility of manipulating the near field on a subwavelength scale. We develop a theoretical formulation for coupled chains of metamaterial elements allowing the tailoring of their guiding properties in the near field. In a comprehensive analysis modes of coupled waveguides supporting forward and/or backward waves are identified and the corresponding hybridization mechanisms for dispersion equations of magnetoinductive waves are determined. Analytical predictions are verified both experimentally and numerically on a variety of coupled waveguides. The approach can be employed for the design of near-field manipulating devices. © 2006 The American Physical Society.